Analysis of Erosion Hazard Index In Konaweha Sub-Watershed In Laosu Village, Bondoala Sub-District, Konawe District - La Baco Sudia; La Ode Midi; Safril Kasim; -, La Ode Muhammad Erif; La Gandri (University of Jember, 2025)
The Erosion Hazard Index (EHI) is the ratio between potential erosion rate and allowable erosion rate, influenced mainly by climate (rainfall) and soil factors such as slope, slope length, land use, conservation practices, and soil physical-chemical properties. This study aims to determine the EHI in the Konaweha Sub Watershed, Laosu Village, Bondoala District, Konawe Regency, using the Universal Soil Loss Equation (USLE): A = R·K·L·S·C·P, compared to allowable erosion (ETol). Analysis shows variation in EHI across different land units, classified into low, moderate, and high hazard levels. The lowest EHI (0.02) occurs in dry/former agricultural land (U-06), moderate EHI (1.43) in swamp areas (U-04), and the highest EHI (6.71) in settlements (U-02). These differences arise due to varying potential erosion and tolerance levels, with major erosion drivers being rainfall erosivity, soil erodibility, slope steepness, and slope length. In general, residential lands (U-02 and U-03) have high erosion hazards (EHI 6.15–6.71), while dry/waste agricultural lands (U-08) and swamps (U-04) fall under moderate hazard. Other land uses such as mixed gardens (U-05) and built-up lands (U-01) show low erosion hazards (EHI <1.0). To mitigate erosion risks, the study recommends conservation practices such as contour planting and maintaining vegetation cover, especially in high-risk areas, to ensure sustainable land use and reduce soil degradation.